Original PaperChanges in the long bone in the new experimental model of osteomyelitis aseptica chronica in rats - Kaczmarczyk-Sedlak, Ilona (Reumatologia/Rheumatology, 2006)
The aim of the present study was to investigate the new model of osteomyelitis aseptica chronica on the morphometry of the bone and haematological parameters in rats. The experiment was carried out on male Wistar rats divided into 2 groups in which osteomyelitis was induced (3 or 6 weeks) and 2 respective control groups. The osteomyelitis was induced using the implant of an aseptic cotton fibre inserted into the marrow cavity of the femur of rats. After 3 or 6 weeks of the experiment, the animals were killed. The macrometric parameters (mass, length, diameter of the diaphysis and epiphysis) and histomorphometric parameters of the femur (transverse cross-sectional area of the diaphysis and of the marrow cavity, transverse growth, width of the osteoid, width of the trabeculae in the epiphysis, and width of the epiphyseal cartilage) were studied. Haematological investigation of the blood and marrow was also carried out. The applied experimental model may be used to induce osteomyelitis aseptica chronica (6 weeks). A decrease in the number of erythroblastic system cells and increases in the number of myeloblastic, lymphoblastic and reticular-endothelial system cells of the bone marrow of the bone containing the implant were observed. Also, an increase in the transverse cross-sectional area of the diaphysis and a decrease in the transverse cross-sectional area of the marrow cavity, increases in the endosteal and periosteal transverse growth, an increase in bone mass and deformation of the bone containing the implant were observed.